(untitled) (Revista de Artes Marciales Asiáticas, 2012)
Kumi-uchi, literally “grasp and strike”, is a traditional Japanese fighting art mainly based on non-armed techniques. As such, kumi-uchi is consider to have emerged as a complement to the main samurai martial arts, so as to face those difficult situations in which the samurai lost his most powerful weapons. This paper studies the art of kumi-uchi from the Kaze no Ryu school standpoint. The meaning and extension of kumi-uchi, its main aspects, types, dimension and evolution are analyzed. Similarly, we place kumi-uchi into the Kaze no Ryu martial curriculum and reflect on its importance in martial artists’ education.